Avian Sensory Kit for Enhancing Accessible Avitourism for Visually Impaired Tourists in Kota Tinggi, Johor - Mat Zaidi, Nurul Farisyah; Norazlimi, Nor Atiqah (Enhanced Knowledge in Sciences and Technology, 2025)
Avitourism or birdwatching tourism has become an increasingly important subsector in ecotourism. Despite its popularity, avitourism has posed challenges to those with vision disabilities. To overcome these challenges, accessible avitourism was introduced to this study which aims to provide inclusive avitourism to visually impaired people. The study was conducted from early August to the end of August 2024 in selected areas of Kota Tinggi, Johor. The objectives of this study were to provide checklist of avian species present in selected areas of Kota Tinggi, Johor, develop an avian sensory kit to enhance the accessibility of the avitourism experience for visually impaired tourists in Kota Tinggi, Johor and to evaluate the effectiveness of the avian sensory kit for visually impaired tourists and local guides in Kota Tinggi, Johor.  A total of 46 bird species were recorded and six species were selected for the kit development based on the criteria that highlighted their value as nature tourism products. An avitourism program was held in November 2024 to introduce the kit to visually impaired tourists. Positive feedback was received from the visually impaired tourists and stakeholders for the avian sensory kit indicating that this kit successfully improved the experience of visually impaired tourists in participating in this accessible avitourism program. Thus, this highlights the potential of accessible avitourism to promote social change by fostering inclusivity within the avitourism and broader tourism industry.